1997
DOI: 10.1139/b97-069
|View full text |Cite
|
Sign up to set email alerts
|

Growth of four bark-beetle-associated blue-stain fungi in relation to the induced wound response in Norway spruce

Abstract: Twenty-five-year-old Norway spruce trees (Picea abies) were inoculated with four blue-stain fungi. Each tree was inoculated three times with each fungus and three times with sterile agar as a control, giving a total of 15 inoculations per tree. There was little variation in the extent of phloem necrosis produced in response to the different fungi, but 5 weeks after inoculation necroses induced by Cerntocystis polorlica and Atnbrosiella sp. were significantly longer than those for the other fungi. At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(46 reference statements)
6
11
0
Order By: Relevance
“…The symptom development was less intensive compared with the results by Yamaoka et al (2000). The rapid enlargement of the desiccated xylem in horizontal and longitudinal directions within 4 weeks after inoculation confirms the observations of Krokene and Solheim (1997) on Norway spruce. The dye injection tests and anatomical studies indicated that sap ascent of the saplings that had been inoculated with C. polonica was considerably reduced or even blocked prior to the appearance of visible foliar symptom and resinosis from inoculation wounds.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The symptom development was less intensive compared with the results by Yamaoka et al (2000). The rapid enlargement of the desiccated xylem in horizontal and longitudinal directions within 4 weeks after inoculation confirms the observations of Krokene and Solheim (1997) on Norway spruce. The dye injection tests and anatomical studies indicated that sap ascent of the saplings that had been inoculated with C. polonica was considerably reduced or even blocked prior to the appearance of visible foliar symptom and resinosis from inoculation wounds.…”
Section: Discussionsupporting
confidence: 82%
“…In the present experiment, the distribution of fungal hyphae was very restricted during the early period of infection until appearance of foliar symptoms. The finding that fungal hyphae are not present in the margin of the dry zones at the initiation of needle discolouration is in agreement with Hobson et al (1994) and Krokene and Solheim (1997). The finding that fungal hyphae are not present in the margin of the dry zones at the initiation of needle discolouration is in agreement with Hobson et al (1994) and Krokene and Solheim (1997).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…After lowdensity inoculation, however, lesion length alone is not a good measure of the resistance of the tree or of fungal virulence. Here lesion length was about the same as in a lowdensity study in Norway spruce after a corresponding incubation time (Krokene and Solheim 1997). In general, small lesions indicate either the weakness of the aggressor or the resistance of the host.…”
Section: Terpenessupporting
confidence: 62%
“…Similar conclusions have been reached in other studies based on a comparable experimental design , Nagy et al 2000, Krekling et al 2003, Krokene et al 2003. Defense responses of coniferous trees to pathogen infection include rapid cell death and accumulation of secondary metabolites at the infection site (e.g., phenolic and resinous compounds), resulting in discrete necrotic lesions (Berryman 1972, Nicholson and Hammerschmidt 1992, Krokene and Solheim 1997. Tissue discoloration and necrosis are associated with oxidation and polymerization of accumulating phenols.…”
Section: Cellular and Tissue Reactionssupporting
confidence: 78%